Sosial Budaya Pembentuk Permukiman Masyarakat Tengger Desa Wonokitri, Kabupaten Pasuruan - Ayuninggar, Dianing Primanita; Antariksa, Antariksa; Wardhani, Dian Kusuma (Jurnal Tata Kota dan Daerah, 2013)
Traditional settlement is a manifestation of the socio-cultural society that has a very important role in the formation of spatial structures in a rural settlement. Settlement of Wonokitri village formed from socio-cultural values of Tengger society which is seen from the application of socio-cultural activities in the people’s daily lives. The purpose of this study was to identify and analyze the socio-cultural characteristics that form the settlement in Wonokitri village. The method used is descriptive exploratory method, behaviour mapping analysis with person centered mapping method and family tree analysis. The study results showed that the linkage between the activities and the space as a place where it happen form movement patterns (trajectory) and the hierarchy of a specific space in the settlement of Tengger society in Wonokitri village. Cultural space and ritual space formed in the settlement which is grouped into space scale micro, meso and macro based on the use of spatial scale. In terms of the importance of ritual space, temples, padhanyangan, sacred cemetery are the main sacred spaces and have a major role in the implementation of socio-cultural activities in Wonokitri village. Movement patterns that formed from the implementation of socio-cultural activities hierarchically describe the movement, the movement from the sacred place to the profane, or otherwise. There are similarities in the pattern of phases of activity, movement patterns and use of space in some activities, especially activities related to the ritual.Keywords: Socio-cultural, Space Pattern, Tengger